Assessment of serum and urinary levels of neutrophil gelatinase-associated lipocalin in correlation with albuminuria in nondiabetic obese patients - Nearmeen M Rashad; Nora M Said; George Emad; Ahmed F Gomaa; Heba M Kadry (SpringerOpen, 2019)
Background Obesity, a new pandemic, is associated with an increased risk of death and morbidity. Obesity-related glomerulopathy is an increasing cause of end-stage renal disease. Neutrophil gelatinase-associated lipocalin (NGAL) is a neutrophil-expressed inflammatory protein that is increased in different diseases. The objective of the current study was to evaluate the predictive performance of serum and urinary NGAL in obese patients and to clarify its possible relationship with different stages of albuminuria in nondiabetic patients. Patients and methods This cross-sectional study was conducted on 55 obese patients and 40 healthy individuals as a control group. The enrolled patients were divided into three groups according to the level of albuminuria. Serum and urinary NGAL (ng/ml) were measured by enzyme-linked immunosorbent assay kits. Results Serum and urinary NGAL levels were significantly higher in obese (354.44±121.2 and 213.22±10.8, respectively) compared with healthy controls (44.21±11.2 and 13.9±6.3, respectively; P<0.001). Moreover, there were higher significant values of serum NGAL in patients with macroalbuminuria (488.65±44.53) and microalbuminuria (264.33±25.53) compared with patients with normoalbuminuria (122.48±4.53, P<0.001) and higher significant values of urinary NGAL in patients with macroalbuminuria (363.84±32.53) and microalbuminuria (112.19±26.53) compared with patients with normoalbuminuria (32.17±10.53, P<0.001). Serum and urinary NGAL levels were statistically significant predictors of albuminuria among obese patients. In addition, our results observed that BMI, waist/hip ratio, urinary albumin, estimated glomerular filtration rate, and urinary albumin-creatinine ratio were independently correlated with serum NGAL, whereas BMI, waist/hip ratio, and urinary albumin were the only variables that were independently correlated with urinary NGAL. Conclusion The higher levels of serum and urinary NGAL in obese patients compared with healthy group were strongly correlated with urinary albumin-creatinine ratio and cardiometabolic risk factors.